APPLYING AFFINITY GROUPING STRATEGY THROUGH PROCESS-BASED CLASSIFICATION ESSAY WRITING TO IMPROVE THE STUDENTSâ WRITING ABILITIES - Aulia, Vivi (Vidya Karya Jurnal Kependidikan, 2013)
This article is a report of one-cycle Classroom Action Research conducted to the fifth undergraduate English majors in STKIP-PGRI Banjarmasin. This study was conducted to implement the strategy of affinity grouping which became an alternative to solve the studentsâ writing problem of exploring and generating ideas which, in turn, improved their writing abilities. The instruments used for collecting data were field notes, questionnaires, and studentsâ classification essay projects. It was found out that affinity grouping not only improved studentsâ writing abilities but also helped them figure out what topic to write, developed their general ideas, and elaborated satisfying information and sufficient details of their ideas generation.